2015
DOI: 10.1097/iae.0000000000000300
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intravitreal Triamcinolone Acetonide Versus Intravitreal Bevacizumab as the Primary Treatment of Clinically Significant Macular Edema

Abstract: The short-term efficacy of IVTA and IVB on treating clinically significant macular edema varied with different optical coherence tomography findings. In clinically significant macular edema combined with serous retinal detachment, IVTA may be more favorable than IVB in CRT reduction and BCVA improvement. In patients with diffused macular thickening, IVB may be better than IVTA in macular thickness reduction, although this does not translate to a significant improvement in BCVA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 30 publications
1
19
1
3
Order By: Relevance
“…Additionally, comparison of mean visual gains in the subgroup with serous macular detachment during the first year revealed no significant difference between groups 1, 2, and 3 (4.0, 6.0, and 6.0 letters, respectively, p = 0.342). This finding contradicts previous conceptions which favor intravitreal triamcinolone over intravitreal bevacizumab in eyes with serous retinal detachment in terms of visual benefit [16].…”
Section: Discussioncontrasting
confidence: 56%
“…Additionally, comparison of mean visual gains in the subgroup with serous macular detachment during the first year revealed no significant difference between groups 1, 2, and 3 (4.0, 6.0, and 6.0 letters, respectively, p = 0.342). This finding contradicts previous conceptions which favor intravitreal triamcinolone over intravitreal bevacizumab in eyes with serous retinal detachment in terms of visual benefit [16].…”
Section: Discussioncontrasting
confidence: 56%
“…Recent studies have even shown that IVTA has a positive effect on those forms of DME that are refractory to Retinal laser treatment [17]. Various studies including that of Masahiko Shimura et al; [18] Liu Q1 et al; [19] etc. demonstrated that Triamcinolone acetonide is more efficient is reducing DME and provided better and longer lasting visual improvement relative to Bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
“…Triamcinolone acetonide is a hydrophobic small molecule drug. Its suspension is commercially available and has been used as a sustained release formulation through intravitreal or subtenon injection to treat various chorioretinal disorders [33][34][35]. TA has been evaluated with suprachoroidal injection and Olsen et al reported that TA remained in the local ocular tissue for at least 120 days following a 12 μL TA suspension suprachoroidal cannulation [10].…”
Section: Discussionmentioning
confidence: 98%